2005
DOI: 10.1038/sj.ijo.0803177
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and potential mechanisms of obesity-induced oxidant stress in humans

Abstract: Objective: Oxidative stress may be the unifying mechanism underlying the development of comorbidities in obesity. Evidence suggests that a clustering of sources of oxidative stress exists in obesity: hyperglycemia, hyperleptinemia, increased tissue lipid levels, inadequate antioxidant defenses, increased rates of free radical formation, enzymatic sources within the endothelium, and chronic inflammation. Method: This review provides a summary of the available evidence on systemic oxidative stress in humans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
486
5
29

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(566 citation statements)
references
References 116 publications
29
486
5
29
Order By: Relevance
“…Although the unadjusted comparison showed that Sepp1 levels were significant higher in subjects from the high-risk area (~12% higher) than those from the low-risk area, adjustment by lifestyle and dietary co-variables attenuated the association. Obesity has been postulated to be associated with oxidative stress (46,47). It is likely that once the obesity persists, sources of the antioxidant enzymes become depleted, leading to a low level of GPx activity, as we found in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Although the unadjusted comparison showed that Sepp1 levels were significant higher in subjects from the high-risk area (~12% higher) than those from the low-risk area, adjustment by lifestyle and dietary co-variables attenuated the association. Obesity has been postulated to be associated with oxidative stress (46,47). It is likely that once the obesity persists, sources of the antioxidant enzymes become depleted, leading to a low level of GPx activity, as we found in our study.…”
Section: Discussionsupporting
confidence: 69%
“…We also found increased levels of TBARS among patients with NAFLD. High OS has been described previously to be associated with obesity [28,29]. Also, there is accumulating evidence that mitochondrial dysfunction (more particularly respiratory chain defects) plays an important role in the pathophysiology of advanced forms of NAFLD, whatever its initial cause [29,30].…”
Section: Discussionmentioning
confidence: 87%
“…This oxidative stress triggers the development of insulin resistance and is responsible of some of the comorbidities that accompany obesity (Urakawa et al, 2003, Vincent andTaylor, 2006), including the inhibition of preadipocyte differentiation that may contribute to age-associated adipose tissue dysfunction (Findeisen et al, 2011). In addition, animal studies show that oxidative stress in adipose tissue contributes to dysregulation of adipokine production via PPARγ-responsive element in the adiponectin gene promoter and to obesity (Furukawa et al, 2004;Houstis et al, 2006).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The main strategies that have been implemented in the reduction of obesity-related oxidative stress are weight loss and antioxidant supplementation. Weight loss reduces enhanced oxidative stress and different methods, such as physical activity, caloric restriction, and surgical intervention, have been proposed to combat free radicals and reduce adipose tissue (Vincent and Taylor, 2006). Regarding antioxidant supplementation, Yeon et al (2011) have shown that the plasma total antioxidant capacity significantly increases as the quartile value of dietary fiber and antioxidant vitamins, such as vitamin A, β-carotene, vitamin C, and vitamin E increases, whereas 8-OHdG level is negatively associated with vitamin A and β-carotene intake.…”
Section: Oxidative Stressmentioning
confidence: 99%